Physicochemical characterization, kinetic parameters, shelf life and its prediction models of virgin olive oil from two cultivars (“Arbequina” and “Moroccan Picholine”) grown in Morocco - Gagour Jamila; Oubannin Samira; Ait Bouzid Hasna; Bijla Laila; El Moudden Hamza; Sakar El Hassan; Koubachi Jamal; Laknifli Abdellatif; Gharby Said (Oilseeds and fats, crops and lipids, 2022)
This works aimed at investigating shelf-life behavior of extra virgin olive oil (EVOO) extracted from two cultivars “Arbequina” and “Moroccan Picholine” as a function of storage time (8 weeks) at accelerated conditions (60 °C). Our outcomes revealed significant variations between EVOOs from both cultivars in terms of the investigated physicochemical characteristics. These were also affected by storage time and temperature except for fatty acids, for which storage time had no significant effects. While the changes in tocopherols showed a drastic reduction ranging from 48.18 (“Moroccan Picholine”) to 62.62% (“Arbequina”). Indeed, the changes of quality indices showed a linear increase. Moreover, “Arbequina” oil was the first to exceed the established upper limits for EVOO label. An increase in oxidation rate was observed with increasing temperature when oils were oxidized at six elevated temperatures (373, 383, 393, 403, 413 and 423 °K) under Rancimat test conditions. The natural logarithms of the kinetic rate constant varied linearly with respect to temperature, with temperature coefficient (TCoeff) ranging from 7.31 × 10−2 in “Arbequina” to 7.51 × 10−2 K−1 found in “Moroccan Picholine”. This had higher oxidative stability and shelf life as compared to “Arbequina”. These outcomes were confirmed by kinetic parameters of oxidative stability including reaction rate constant as well as Arrhenius equation and thermodynamic parameters.